An investigation of the role played by the youth and their involvement in politics from 1980 to 2016”: case study Mbare - Shamuyarira, Tendai (Midlands State University, 2017)
This study investigates the role played by the youth and their involvement in politics from 1980 to 2016, basing on Mbare. The will look from the transition of Chibwidos and Mujibhasi from the war and their integration into the society and the army. The formation of the 5th Brigade and its deployment in Matabeleland and its practices on the local people which led to more than 20 000 deaths including women and children, due to hunger, torture and abductions. The failure of the government to act and rescue the people as it was part of the strategy which was to prolong its stay in power. The research also looks at the role played by the youths in land invasions of 2000 and the damage it brought to the communities and the country at large. Also brings to light the emergence of a new generation youths leaders who became active in politics and violence that occurred in Mbare. This study also looks at the formation of the youth brigades in 2000 by late Border Gezi and the role it played in ensuring that ZANU (PF) stayed in power. Furthermore the research looks at Chipangano and its extractives practises in Mbare, which led do devastation of properties, loss of human lives, torture and abductions. All this crimes are against humanity from 1980 to 2016 how they have gone unpunished, because they are done in the name of ZANU (PF). Interviews, books and internet sources have been extensively used by the researcher in gathering information. Personal observation has also allowed the researcher to compile the facts and finding of the study in a chronological manner.